2014
DOI: 10.1155/2014/474510
|View full text |Cite
|
Sign up to set email alerts
|

One‐Year Results of an Algorithmic Approach to Managing Failed Back Surgery Syndrome

Abstract: Failed back surgery syndrome refers to persistent back pain following back surgery. The optimal course of treatment for this syndrome varies according to the patient and the etiology of the pain. This study describes the application of a treatment algorithm for failed back surgery syndrome, focusing on the use of epiduroscopy, a novel technique that is useful for diagnosis and treatment of this syndrome. Diagnoses and treatment success after one year of follow-up are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 15 publications
0
29
1
2
Order By: Relevance
“…FBSS is a challenging pain indication with various treatment options. For example, a recent review identified 8 different treatment modalities for FBSS, ranging from noninvasive to surgical, and a large prospective study of FBSS patients described an iterative 6‐step treatment algorithm requiring up to a year for implementation . It is likely that the wide variety of FBSS pain generators and the variability in pre‐ and postsurgical patient characteristics (some of which can only be identified in retrospect) contribute to the dissatisfying low rate of robust pain relief across all treatments.…”
Section: Discussionmentioning
confidence: 99%
“…FBSS is a challenging pain indication with various treatment options. For example, a recent review identified 8 different treatment modalities for FBSS, ranging from noninvasive to surgical, and a large prospective study of FBSS patients described an iterative 6‐step treatment algorithm requiring up to a year for implementation . It is likely that the wide variety of FBSS pain generators and the variability in pre‐ and postsurgical patient characteristics (some of which can only be identified in retrospect) contribute to the dissatisfying low rate of robust pain relief across all treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this cut-off point for evaluation of procedural success; Avellanal et al 18 defined treatment success as ≥ 50% long-term pain relief maintained during the first year of follow-up. Also, Manchikanti et al 35 documented that the summary measure for pain was ≥ 50% reduction of pain in at least 50% of patients, or at least a threepoint decrease in pain scores; for disability scores the summary measure was ≥ 50% reduction in disability in at least 40% of …”
Section: Discussionmentioning
confidence: 99%
“…18 • Patients' satisfaction with the procedure was assessed using four-point scale questionnaire with 4 = very satisfied and 1 = very dissatisfied. Willingness to receive treatment again if pain persists or recurs was checked using a five-point scale questionnaire with 5 = definitely will and 1 = definitely will not.…”
Section: Evaluations Of Clinical Outcome Outcome Measuresmentioning
confidence: 99%
“…(35)(36)(37) que puede utilizarse en caso de problemas de acceso por el hiato sacro. Para realizar este procedimiento se inserta una aguja epidural 14g (tuohy, Coudé) en el espacio interlaminar L5-S1 con técnica de pérdida de resistencia y ayudados por fluoroscopia.…”
Section: Tiempo Quirúrgicounclassified